Comparative study for magnetized flow of nanofluids between two parallel permeable stretching/shrinking surfaces. (December 2021) - Nayak, M.K.; Shaw, S.; Waqas, Hassan; Makinde, O.D.; Alghamdi, Metib; Muhammad, Taseer
Abstract: The current study intended to discuss a comparative study on the three dimensional Casson nanofluid with nonlinear radiative MHD flow and heat transfer aspects between two parallel stretching/shrinking surfaces. The mathematical models for momentum and temperature are established by employing the boundary layer flow of fluids with spinel-type ferrite M n F e 2 O 4 nanoparticles being distributed in Pure Water/ ( H 2 O ) as the base fluid. Remarkable models like Maxwell-Garnett and Patel models are inserted in view of thermal conductivity augmentation. The suitable similarity transformations are adopted for converting the governing non-linear partial differential equations into non-dimensional ODE's and obtaining the relevant parameters for discussion. The major outers of the present study are axial velocity F ′ ( η ) peters out with amplifying β subject to stretched and shrunk surfaces in relation to both Maxwell-Garnett and Patel models. Growing θ w and n exhibits opposite effect on heat transfer rate.